2016
DOI: 10.1152/ajpheart.00107.2016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of graded changes in oxygen and carbon dioxide tension on coronary blood velocity independent of myocardial energy demand

Abstract: Boulet LM, Stembridge M, Tymko MM, Tremblay JC, Foster GE. The effects of graded changes in oxygen and carbon dioxide tension on coronary blood velocity independent of myocardial energy demand. Am J Physiol Heart Circ Physiol 311: H326 -H336, 2016. First published May 23, 2016 doi:10.1152/ajpheart.00107.2016.-In humans, coronary blood flow is tightly regulated by microvessels within the myocardium to match myocardial energy demand. However, evidence regarding inherent sensitivity of the microvessels to change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 57 publications
3
21
0
Order By: Relevance
“…The contrasting findings may, in part, be due to the nature of our two scenarios. During acute hypoxia prior to LBPP, no change in ventricular volumes was observed, nor would it be expected (Boulet, Stembridge, Tymko, Tremblay, & Foster, 2016). With sustained hypoxic exposure, but it is well established that ventricular volumes decrease (Stembridge & Levine, 2019), especially in the left heart.…”
Section: Discussionmentioning
confidence: 91%
“…The contrasting findings may, in part, be due to the nature of our two scenarios. During acute hypoxia prior to LBPP, no change in ventricular volumes was observed, nor would it be expected (Boulet, Stembridge, Tymko, Tremblay, & Foster, 2016). With sustained hypoxic exposure, but it is well established that ventricular volumes decrease (Stembridge & Levine, 2019), especially in the left heart.…”
Section: Discussionmentioning
confidence: 91%
“…All echocardiographic measurements were collected by a trained sonographer (M. Stembridge) on a commercially available ultrasound system (Vivid E9; GE, Fairfield, CT) using a broadband M5S 5 MHz or a 3-V three-dimensional array transducer. In a previous study, the Cronbach's ␣-reliability test revealed ␣ values of 0.81 and 0.89 for both max and mean LAD velocities, respectively, suggesting good consistency between LAD velocity measurements (5). Participants assumed a left lateral position to allow for data collection.…”
Section: Experimental Measuresmentioning
confidence: 87%
“…Using observer-independent software, VTI is calculated as the integral of individual velocities across the cardiac cycle. Participants who had at least one suboptimal image were excluded before analyses (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia and hypercapnia affect the systemic, pulmonary, and coronary circulation and may thus influence the echocardiographic appearance indirectly. In most clinical scenarios, the underlying pathology leading to respiratory derangement, including congestive heart failure, PE, and cardiomyopathy, dominates the echocardiographic picture.…”
Section: Echocardiographic Changes Due To Acute Respiratory Failurementioning
confidence: 99%